Chemically sensitized ormosil-modified electrodes-Studies on the enhancement of selectivity in electrochemical oxidation of hydrogen peroxide - Pandey P.C.; Singh B.; Boro R.C.; Suri C.R. (My University, 2025)
The chemically sensitized ormosil-modified electrodes were made by encapsulating potassium ferricyanide together with organic-ionophore (dibenzo-18-crown-6/Nafion) within ormosil films. The modified electrodes were studied in details from following angles; (1) the effect of variation in potassium ferricyanide concentration in ormosil films; (2) the effect of variation in dibenzo-18-crown-6 concentration in ormosil films; (3) effect of pH on the electrochemistry of ormosil-modified electrodes, and (4) variation in the microstructure of ormosil's films as a function of chemical sensitizers based on atomic force microscopy. Another remarkable contribution of such films based on the bilayer configuration was investigated and the results justified further enhancement in the selectivity for electrochemical sensing of peroxide. Two approaches of bilayer configuration were adopted based on the absence and the presence of chemical sensitizers (Nafion/crown ether) in the upper layer. Excellent results of peroxide sensing were recorded with remarkable finding as given below: (1) introduction of bilayer configuration reduced the sensing of interfering analytes like ascorbic acid, (2) the presence of crown ether in the upper layer caused enhancement in peroxide sensing, (3) the presence of crown ether in the upper layer and Prussian blue in the lower layer increased the detection limit of peroxide sensing to 0.1 μM as compared to that of 0.5 μM recorded in earlier publication, (4) the presence of the bilayer resulted in an increase in the linear range of peroxide sensing, (5) the single layer Prussian blue modified electrode showed electrocatalytic oxidation of ascorbic acid whereas the same with the bilayer containing crown ether reduced the electrochemical sensing of ascorbic acid, followed by an increase in peroxide sensing, and (6) the kinetics of peroxide reduction on the bilayer ormosil-modified electrode was reduced as compared to that on the single layer modified-electrode. The results based on cyclic voltammetry showed a linear increase in cathodic and anodic peak currents with increasing the concentration of ferricyanide within the ormosil film. The results on the effect of pH suggested that lowering of pH caused faster reduction as well as oxidation of peroxide whereas the reverse was recorded with increasing the pH. An increase in dibenzo-18-crown-6 concentration resulted higher oxidation current of peroxide, followed by a decrease in reduction of the same. The results of cyclic voltammery and amperometric measurements were also reported in this communication. The calibration curve of peroxide sensing using the bilayer ormosil-modified electrodes was reported. © 2006 Elsevier B.V. All rights reserved.